Altered Affect and Increased CLIP+ B cells in the Meningeal Lymphatics of 5xFAD mice are mitigated by antagonizing MHCII‐associated invariant chain (CLIP). (20th December 2022) - Iannucci, Jaclyn; Beevers, Samantha; Tobin, Richard; Newell‐Rogers, M. Karen; Shapiro, Lee A.
Abstract: Background: Depression often occurs prior to Alzheimer's disease (AD) and both depression and AD have been linked to immune mechanisms. A key role for activated B cells in AD pathogenesis was recently identified. The study found that B cell depletion reduced Aβ plaque accumulation, neuroinflammation, and behavioral deficits in three AD transgenic mouse models. Our work has shown that treatment with a peptide antagonist for Major histocompatibility complex class II (MHCII) invariant peptide (CLIP), a key component in the transition between innate and adaptive immunity, results in selective depletion of pro‐inflammatory, CLIP+ve B cells and neuroprotection. We hypothesized that selective depletion of CLIP+ve B cells in the 5xFAD model of AD would reduce depression‐associated behavioral deficits. Method: 11‐week‐old male WT and 5xFAD mice underwent social interaction and burrowing pre‐testing. 12‐week‐old mice were treated once with a competitive antagonist peptide (CAP) or vehicle, followed by social interaction and burrowing testing once a month for 5 months. 6 months post‐treatment, meningeal lymphatics were collected, stained, and analyzed flow cytometrically for markers of B cells (CD19), T cells (CD3), and CLIP. Result: Affective alterations were observed in 5xFAD mice as early as 11 weeks of age and persisted up to 9 months of age. CAP treatment in 5xFAD mice protected against an age‐associated decline in social interaction. At 9 months of age 5xFAD mice were found to have significantly more B cells and CLIP+ve B cells in the meningeal lymphatics when compared to age‐matched WT, and CLIP+ve B cells were significantly decreased by a single CAP injection at 3 months of age. Conclusion: A key function of B cells is their role as antigen presenting cells (APCs). CLIP occupies the MHCII antigen binding groove until it is displaced by antigen to be presented to CD4+ T cells, marking the transition between an innate and an adaptive immune response. Our findings suggest that 5xFAD mice exhibit depression‐associated behavior by 11 weeks of age, that CLIP+ve cells are elevated in 5xFAD mice, and that antagonizing CLIP depletes these B cells and functionally protects mice genetically predisposed to AD.